2023
DOI: 10.3390/foods12040875
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations and the Mechanism Underlying Cryoprotective Activity of Peptides from Enzymatic Hydrolysates of Pseudosciaena crocea

Abstract: Antifreeze peptides are a class of small molecule protein hydrolysates that protect frozen products from cold damage under freezing or subcooling conditions. In this study, three different Pseudosciaena crocea (P. crocea) peptides were from pepsin, trypsin, and neutral protease enzymatic hydrolysis. It aimed to elect the P. crocea peptides with better activity through molecular weight, antioxidant activity, and amino acid analysis, as well as to compare the cryoprotective effects with a commercial cryoprotecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This trend aligned with the results obtained by Liu et al [50]. In contrast, MT led to the lowest Ca 2 +-ATPase activity and sulfhydryl content, suggesting that the high temperature during MT treatment led to severe protein denaturation and degradation, substantially damaging the structure and integrity of protein, with a resulting decrease in Ca 2+ -ATPase activity and a sharp decline in sulfhydryl content [51]. However, protein oxidation was also found to be the least extensive in the FWT group, as evidenced by higher Ca 2+ -ATPase activity and greater sulfhydryl content, which are indicators of protein integrity.…”
Section: Impact Of Thawing Methods On Protein Oxidation In a Neglectussupporting
confidence: 90%
See 1 more Smart Citation
“…This trend aligned with the results obtained by Liu et al [50]. In contrast, MT led to the lowest Ca 2 +-ATPase activity and sulfhydryl content, suggesting that the high temperature during MT treatment led to severe protein denaturation and degradation, substantially damaging the structure and integrity of protein, with a resulting decrease in Ca 2+ -ATPase activity and a sharp decline in sulfhydryl content [51]. However, protein oxidation was also found to be the least extensive in the FWT group, as evidenced by higher Ca 2+ -ATPase activity and greater sulfhydryl content, which are indicators of protein integrity.…”
Section: Impact Of Thawing Methods On Protein Oxidation In a Neglectussupporting
confidence: 90%
“…MT had the fastest thawing rate and the smallest TVB-N value, but exposure to uneven heating and excessive temperatures during this process caused the myofibrillar fibers of the octopus meat to contract and break, causing the meat to appear burnt, and resulting in an unfavorable color after thawing, in addition to the highest thawing and cooking loss rates. In contrast, FWT had the advantages of a short thawing time, minimum thawing loss rate and cooking loss rate, high content of non-flowing water, maximum water-holding capacity, and good water retention; the color of the octopus was excellent after the completion of this process (with In contrast, MT led to the lowest Ca 2 +-ATPase activity and sulfhydryl content, suggesting that the high temperature during MT treatment led to severe protein denaturation and degradation, substantially damaging the structure and integrity of protein, with a resulting decrease in Ca 2+ -ATPase activity and a sharp decline in sulfhydryl content [51]. However, protein oxidation was also found to be the least extensive in the FWT group, as evidenced by higher Ca 2+ -ATPase activity and greater sulfhydryl content, which are indicators of protein integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Turbot samples were processed as described in our previous study [ 13 , 14 ]. Three single turbots were immediately stunned, slaughtered, and skinned, then preserved on ice for transportation to the laboratory within 1 h before the fish presented rigor mortis.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…It has been reported that antifreeze peptides generally have specific amino acid sequence lengths and molecular weights less than 2 kDa [ 11 , 12 ]. Our prior study reported that a tryptic hydrolysate (TH) of croceine croaker significantly enhanced the physicochemical attributes of fillets, including their water-holding capacity, texture, oxidative stability, and thermal stability after cold storage, presenting comparable antifreeze capabilities to traditional agents [ 13 ]. However, few studies have assessed the cryoprotective effects and mechanisms in fish after the isolation and purification of antifreeze peptides.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the antifreeze properties of these hydrolysates, the F-T cycle procedure was applied to evaluate the protein and lipid oxidation degree of muscle-rich products, such as fish/shrimp muscle or scallop adductor muscle [ 16 , 17 , 48 ]. Most protein oxidation indices, including sulfhydryl content, carbonyl content, salt-solubility, Ca 2+ -ATPase activity, and MP structure changes, have been found to demonstrate effective antifreeze properties by scavenging vitro free radicals and inhibiting ice crystal transformation [ 46 , 49 ]. For instance, a 0.1% ( w / v ) herring skin type I AFP tested for preventing the frozen denaturation of red sea bream cubes and largemouth bass fillets by effectively inhibiting the passive impact of water–ice phase transition, such as freezing point rise, ice crystal shape/growth, water holding capacity reduction, and water mobility/distribution [ 48 , 50 ].…”
Section: Freezing Protection Of Aquatic Products By Afps and Afptsmentioning
confidence: 99%